Gevrey well-posedness of the 2D micropolar boundary layer equations without structural assumption - Fan Dongyue; Lin Xueyun (EPJ Web of Conferences)
In this paper, we are aimed to obtain the well-posedness theory for the 2D micropolar boundary layer system in Gevrey function space with Gevrey index σ ε (1, 3/2 ] in the absence of the structural assumption. This paper first introduces the Gevrey function space. Then it obtains the a priori estimate. It is worth mentioning that we introduce an auxiliary function u which is of great importance to overcome the loss of tangential derivatives in the system. We discover that the 2D micropolar boundary layer system is well-posed in Gevrey function space.